PENERAPAN METODE DRILL UNTUK MENINGKATKAN KETERAMPILAN MEMBACA NYARING PADA SISWA SEKOLAH DASAR - Karnila, Karnila; Halidjah, Siti; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to describe the improvement of students’ reading aloud using drill methord towards the second grade of SD Negeri 14 Peresak Bengkayang. The method of this research is descriptive in form of classroom action research with collaborative as its charachteristics. Subject of this research is the teacher and students of second grade that is 25 students. The technique of collecting data used is direct observation. The tool of data collection is IPKG I, IPKG II, Students; observation sheets. Technique of data analysis is to calculate the average score of teacher’s ability on planning , implementing, and the students’ improvement of students’ reading aloud using mean formula. This research is done in three cycles. The result of this research is (a) the teacher’s ability on planning (IPKG I) in the first cycle is 3.00, in the second cycle is 3.00, and the third cycle is 3.00. By this, it an be seen there is no improvement in each cycle, and 3,00 is in good category; (b) the teacher’s ability on implementing (IPKG II) in the first cycle is 3.32( good category), in the second cycle improves to 3.86 (very good category), and the third cycle is 3.98(very good category. Meanwhile, the students’ability on reading aloud using drill method is 59.5 in the first cycle, 77.12 in the second cycle, and 87.68 in the third cycle with all of the students passed the minimum score. By those data above, it can be concluded that there is an improvent on students’ ability in reading aloud using drill method. Keywords: Reading Aloud, Drill method, Improving